Network neutrality: From policy to law to regulation - Marsden, Christopher T (Manchester University Press, 2017)
This book explains the beginnings of net neutrality regulation in the United States and Europe, and some of the current debate over access to Specialised Services: fast lanes with higher Quality of Service (QoS). It examines the new European law of 2015 and the interaction between that law and interception/privacy. The book takes a deep dive into UK self- and co-regulation of net neutrality. In each of the national case studies, initial confusion at lack of clarity in net neutrality laws gave way to significant cases, particularly since 2014, which have given regulators the opportunity to clarify their legislation or regulation. The majority of such cases relate to mobile net neutrality, and in particular so-called 'zero rating' practices. The book compares results and proposes a regulatory toolkit for those jurisdictions that intend effective practical partial or complete implementation of net neutrality. It sets out a future research agenda for exploring implementation of regulation. The book outlines competition policy's purpose, referring to the exceptionally rigorous recent analysis of competition law suitability to regulate net neutrality by Maniadaki. Having analysed regulatory tools with little chance of success, it then examines what communications regulators actually do: regulating telecoms access based on the UK case study. The book considers whether zero rating poses a serious challenge to Open Internet use. It explores some of the wider international problems of regulating the newest manifestation of discrimination: zero rating. The book also considers the various means by which government can regulate net neutrality.